Research Hotspots and Trends of NK Cell Immunotherapy for Acute Myeloid Leukemia: A Bibliometric Analysis From 2000 to 2023 - Shupeng Chen MD; Jie Liu MM; Kaiyue Xia MM; Yao Gao MD; Yingjian Zeng PhD (Cancer Control)
Background Natural killer (NK) cell immunotherapy has shown promising therapeutic potential for acute myeloid leukemia (AML), especially with advancements in chimeric antigen receptor-engineered NK cells (CAR-NK) and artificial intelligence (AI). Despite these developments, the field lacks comprehensive bibliometric analyses to identify research hotspots and trends, which could guide future precision treatments. Methods A bibliometric analysis of NK cell immunotherapy for AML was conducted using literature from 2000 to 2023 retrieved from the Web of Science Core Collection database. Data visualization tools like CiteSpace, VOSviewer, and RStudio were employed to analyze publication trends, country contributions, institutional collaborations, influential authors, and research themes. Results The analysis identified 1513 studies, with the United States and China leading global contributions. Notable institutions include the University of Minnesota and MD Anderson Cancer Center. Hot topics include allogeneic NK therapy, CAR-NK cell therapy, and memory-like NK cells. Emerging trends highlight the integration of intelligent NK cells and combinatory therapies, offering promising avenues for AML treatment. Despite progress, challenges such as NK cell expansion, activation, and resistance mechanisms remain critical areas for research. Conclusion This study provides a comprehensive overview of the research landscape, highlighting the transformative potential of NK cell immunotherapy in AML. It underscores the need for international collaboration and continued innovation to overcome existing challenges and advance precision therapies.